Corporate blogs : an exploratory study on lifestyle SMEs in Singapore. - Ong, Serene Ling Ling. (2008)
This study focuses on the use of corporate blogs by a specific group of businesses in Singapore - the lifestyle SMEs. This category of SMEs has been chosen as they are usually business-to-consumers companies, and corporate blogs work best for companies that have an involved and interested customer-base. By exploring the level of knowledge and receptiveness that lifestyle SMEs have to the use of corporate blogs as a CRM marketing and branding tool, this research aims to identify the concerns that SME owners have in harnessing this medium for their businesses and the ways in which the Singapore Government could support their growth in order to create vibrant and resilient SMEs.